MORFOMETRIK SALURAN PENCERNAAN IKAN PARANG-PARANG (Chirocentrus dorab Forsskal 1775) DARI PERAIRAN LAUT BENGKALIS PROVINSI RIAU - Jarmanto '; Yusfiati '; Roza Elvyra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This research was aimed to asses morfometric parameters of digestive tracts especially intestine and stomach of Parang-parang fish (Chirocentrus dorab Forskall 1775). This study was conducted from June to August 2012. The samples were collected using survey method. Fish samples were 76 individuals collected from fisherman in Bengkalis, Riau Province. Parameters which measured were the total body length, length of intestine, fish weight, and stomach weight. Data were analyzed using linear regression which consist of the ratio between stomach weight and fish weight with totalbody length, length of intestine with total body length, ratio between intestine length and total body length with total body length and ratio between weight of intestine and fish weight with total body length. The result indicated that parang-parang fish was considered as carnivorous fish based on the length of its intestine, i.e 0,32-0,43 times of its total body length for male fish and 0,33-0,39 times of its total body length for femalefish. Total body length of parang-parang fish was positively correlated to its intestine length and ratio between intestine length and total body length.